Effects of Milling Time on Nano Rice Husk Ash Particle Size - Ibrahim, Mohammed Nasser; Mohd Haziman, Wan Ibrahim; Sharifah Salwa, Mohd Zuki; Abdullah, Faisal Alshalif; Nindyawati, Nindyawati; Putra Jaya, Ramadhansyah (EDP Sciences, 2023)
This research focuses on the manufacture of nano Rice Husk Ash (nRHA) by ball milling technique and critically analyzes the effect of milling time on particle size. The process starts with collection of raw rice husk from a local rice mill factory, followed by controlled incineration at a temperature of 700°C for 5 hours to get the amorphous RHA. Finally, the nano RHA is prepared by subjecting the RHA to grinding for the different period like 10, 20, 30, and 40 hrs. The particle size was analyzed with FESEM, and it was found that particles got smaller as grinding proceeded, reaching an optimal size of 28 nm following 30 h grinding. Nonetheless, prolonged grinding resulted into particle agglomeration that was caused by Van der Waal forces. Therefore, these findings are significant in that they help to comprehend the morphology changes and particle size alterations in nRHA that may be applied for different uses such sustainable construction materials.